The combined diagnostic value of 5-hmC and PRAME immunohistochemistry in melanocytic neoplasms - Yu, Yanhong; Hosseini, Niloufar; Dodington, David; Wood, Kimberly; Ghazarian, Danny; Kamil, Zaid Saeed (Pathology, research and practice, 2025)
The diagnosis of melanocytic neoplasms, particularly those with borderline morphologic features, remains a challenging area in dermatopathology. 5-hydroxymethylcytosine (5-hmC) and PRAME (PReferentially expressed Antigen in MElanoma) are recent immunohistochemical markers which have been shown to be valuable in distinguishing benign from malignant melanocytic neoplasms. A retrospective cohort of 144 benign, borderline (Spitz nevi, atypical Spitz tumors and dysplastic nevi) and malignant melanocytic tumors at our institution were analyzed for 5-hmC and PRAME expression by immunohistochemistry. Compared to benign nevi, melanoma cases had higher PRAME expression (p < 0.0001) and lower 5-hmC (p < 0.0001) expression. In receiver operator curve analysis, 5-hmC and PRAME were good discriminators between benign and malignant neoplasms; the area under the curve (AUC) was 0.91 for 5-hmC (p < 0.0001) and 0.94 for PRAME (p < 0.001). Subgroup analysis showed that 5-hmC expression was significantly different between dysplastic nevi and melanoma. The combination of PRAME and 5-hmC significantly improved the predictive ability of these markers (AUC 0.97, p < 0.001). Having both PRAME expression of 4 + (> 75 % lesional cells positive) and 5-hmC of < 0.2 was highly specific for malignancy (98 %) with a sensitivity of 61 %. Utilizing 5-hmC and PRAME in conjunction improves their diagnostic value in distinguishing benign from malignant melanocytic neoplasms.